2016
DOI: 10.1016/j.ajog.2016.04.039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of major depression on quality of life after surgery for stress urinary incontinence: a secondary analysis of the Trial of Midurethral Slings

Abstract: Women with major depression who are planning surgery for stress urinary incontinence have worse quality of life than nondepressed women. However, women with major depression improve significantly more than those without major depression such that, at 12 months postoperatively, incontinence severity and quality of life are not different between groups. Sexual function is worse before and after the operation for depressed women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Thus, we suggest that UI symptoms relief also improves anxiety/depression. Siff et al 27 demonstrated the effect of major depression on the outcome of MUS surgery in a secondary analysis of the TOMUS trial, a randomized equivalence trial in which 597 women with SUI were assigned to either retropubic or transobturator MUS surgeries. These authors hypothesized that baseline major depression would negatively affect improvement in quality of life and UI severity after MUS surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest that UI symptoms relief also improves anxiety/depression. Siff et al 27 demonstrated the effect of major depression on the outcome of MUS surgery in a secondary analysis of the TOMUS trial, a randomized equivalence trial in which 597 women with SUI were assigned to either retropubic or transobturator MUS surgeries. These authors hypothesized that baseline major depression would negatively affect improvement in quality of life and UI severity after MUS surgery.…”
Section: Discussionmentioning
confidence: 99%
“…According to Broome, UI affects around 15%–35% of the adult ambulatory population, and its impacts include depression, self-efficacy and poor quality of life (QoL) (7). Depression has also been suggested to be associated with UI (8, 9). Previous studies have found that UI leads to anxiety and hysteria (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Age in women with POP is reported to be an important indicator for quality of life 37 , and quality of life is reported to be highly affected by the negativity experienced in physical mobility, pain, emotional reactions, social isolation, and energy and sleep state 37,[39][40][41][42] . One of the inclusion criteria for this research is to be over age 40 and above.…”
Section: Discussionmentioning
confidence: 99%